The Implementation of WATUTU Media Based on a Role Playing Approach in Pancasila Education for Phase A Elementary Students - Salsabila, Naura Aisya; Somantri, Mubarok (International Conference on Elementary Education, 2025)
This study aims to describe the implementation of the WATUTU media (Wayang Patuh Aturan) based on a role-playing model in Pancasila Education learning for Phase A elementary school students. This research was motivated by the need for innovative and interactive learning media to support students at the concrete operational stage in understanding abstract concepts, particularly rules in Pancasila Education. This study employed a descriptive quantitative approach involving 22 first-grade students at an elementary school in Sukasari District, Bandung. Data were collected through questionnaires, interviews, and documentation. The results showed that the use of WATUTU media integrated with the role-playing model was effective in increasing students' understanding and motivation in learning Pancasila, especially regarding rules. Students responded positively to the media, stating that it was engaging, easy to understand, and helpful in applying Pancasila values in daily life. The findings indicate that integrating visual and interactive media such as WATUTU with role-playing can enhance young learners’ learning experiences and outcomes in Pancasila Education, and it is recommended for broader implementation in early-grade learning contexts.